2018
DOI: 10.1007/s10461-018-2328-6
|View full text |Cite
|
Sign up to set email alerts
|

Making the Link: A Pilot Health Navigation Intervention to Improve Timely Linkage to Care for Men Who have Sex with Men and Transgender Women Recently Diagnosed with HIV in Guatemala City

Abstract: Introduction: Men who have sex with men and transgender women across the globe experience barriers to timely linkage-to-HIV care. Health navigation is a strengths-based approach, originally developed for cancer patients, to address these barriers and provide support. We piloted a health navigation strategy to improve timely linkage-to-care among men who have sex with men and transgender women recently diagnosed with HIV in three sexual health clinics in Guatemala City. Methods: Participants included individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…The current work has implications for intervention and research. It is consistent with evidence supporting efforts to improve the quality of linkage procedures at both the community (Tanner et al, 2016) and health system (Loya‐Montiel et al, 2019) levels. Future interventions to enhance social support, reduce HIV stigma, and provide support to deal with family issues regarding the disclosure of HIV status might be useful, especially for newly diagnosed MSM.…”
Section: Discussionsupporting
confidence: 84%
“…The current work has implications for intervention and research. It is consistent with evidence supporting efforts to improve the quality of linkage procedures at both the community (Tanner et al, 2016) and health system (Loya‐Montiel et al, 2019) levels. Future interventions to enhance social support, reduce HIV stigma, and provide support to deal with family issues regarding the disclosure of HIV status might be useful, especially for newly diagnosed MSM.…”
Section: Discussionsupporting
confidence: 84%
“…24 To address these challenges being tested for HIV and linked to care, our team designed and implemented the first navigation pilot intervention to promote timely linkage to care in Guatemala city in 2014. 25 Based on encouraging results of the pilot and the high levels of satisfaction among participants and clinics, with participants using a mobile application (app), including mode of interaction (in-person or remote), duration of the interaction (in minutes), and content of the interaction (appointment reminder, HIV education, emotional support, etc. ).…”
Section: Methodsmentioning
confidence: 99%
“…Participants reported that peer navigation may help facilitate linkages and help address barriers. Navigation services have been successful in engaging trans women in HIV care [26]. Navigation services, and particularly peer navigators who identify as trans and work in the public health system have been shown to improve HIV care engagement and outcomes and may provide the needed bridge for trans women to link to MHSU services through the fostering of trust, the similarities in background between peer and participant and accessibility of peer navigators [26][27][28][29].…”
Section: Recommendationsmentioning
confidence: 99%
“…Navigation services have been successful in engaging trans women in HIV care [26]. Navigation services, and particularly peer navigators who identify as trans and work in the public health system have been shown to improve HIV care engagement and outcomes and may provide the needed bridge for trans women to link to MHSU services through the fostering of trust, the similarities in background between peer and participant and accessibility of peer navigators [26][27][28][29]. Not only can peer navigators offer support through referrals to ancillary support programs, but they can educate, provide feedback, and motivational interventions to teach about the connection between social and daily stressors with mental health and substance use and may create motivation to engage in MHSU services [28,29].…”
Section: Recommendationsmentioning
confidence: 99%